The Influence of Location, Selling Price, and Type of Items Sold on Traders' Income - Naura Azura Firdausy Chairisa; Budi Prayitno; Eva Wany (Universitas Airlangga, 2026)
This study aims to analyze the effects of location, selling price, and type of items sold on traders' income in the Kota Lama area of ​​Surabaya. The research is motivated by the income disparities among traders, despite revitalization efforts carried out by the Surabaya City Government. This study employs a quantitative method with an associative approach. The population consists of all traders in the Kota Lama area, with the sample selected using purposive sampling, focusing on traders with permanent and semi-permanent stands. Primary data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The findings reveal that location, selling price, and type of products have a positive and significant effect on traders' income. These results suggest that strategic location selection, effective pricing strategies, and the selection of suitable product types are crucial factors in enhancing traders' income in historical and cultural tourism areas. The theoretical implication of this study is that it can contribute to the study of tourism-based MSMEs, which are still rarely explored quantitatively in Indonesian academic literature. On the other hand, the results of this study suggest the need for fair location planning policies based on the region's economic potential. Support could include zoning regulations, access to strategic areas, and guidance for vendors to ensure their products align with the characteristics of tourists.